Portfolio-based learning in nursing education - Saeed-o-zakerin, M; Khorami Markani, A; Khorami Markani, M (Advances in Nursing & Midwifery, 2010)
Background and aim Portfolio is a set of evidence and documents of students, which shows their endeavors, achievements and successes in theoretical or clinical education. It is one of performance appraisal methods by which tutors can evaluate both the process and progress of learning. Portfolios differ according to design objectives that determine their contents. Main components of educational portfolio in nursing include critical incidents, clinical experiences, log book notes, patient interviews, performance observations, critical incident audits and clinical evaluation of nursing students. This study with a comprehensive literature review was intended to assess portfolio-based learning in nursing education. Materials and Methods A comprehensive literature review from 1980 to 2009 with keywords including portfolio, learning and nursing education was carried out by searching Iranian and International databases including Iran Medex, IranDoc, Pub Med, ERIC, Emerald, Science Direct, Pro Quest and Ovid. Findings Studies revealed that portfolio-based learning is used as an educational and testing strategy in developed countries; however, it is not common in Iran, which warrants further investigation. Conclusion According to educationalists, a well-completed portfolio provides written documents with nursing students and their tutors regarding course objectives, learning needs and ways to meet them. This is very effective on achievement of objectives in theoretical and practical lessons and their evaluation. Keywords: Portfolio, Learning, Nursing education. *Corresponding Author: Abdollah Khorami Markani, PhD Student, Faculty of Nursing and Midwifery, Shahid Beheshti University of Medical Sciences, Shariati, Tehran, Iran. E-mail: Khorami.Abdolah@gmail.com